Study on marine and eco resources in Marudu Bay nearing completion - Ongkili - Bernama, (2011)
KOTA Marudu, May 21 (Bernama) - The integrated eco-resources management study conducted on Marudu Bay by a team of researcher has almost been completed, said Science, Technology and Innovation Minister Datuk Seri Dr. Maximus Ongkili.